Academic Right 101: an introduction in a Malaysian context - Abdul Murad, M.H.S. (2013)
The concept of academic rights it greatly misunderstood, even among some university academics. This paper provides a summary of the historical development of the academic rights from the Roman to the modern era. Many documents and declarations advocating academic rights have been produced, and this paper presents a discussion of the recent documents. The major components of academic rights are elaborated. These include university autonomy, university accountability, academic freedom, academic obligations, security of tenure and collegiality. Some remarks are also made on the current situation in Malaysia.